2007
DOI: 10.31899/hiv2.1023
|View full text |Cite
|
Sign up to set email alerts
|

Key findings from an evaluation of the mothers2mothers program in KwaZulu-Natal, South Africa

Abstract: from the mothers2mothers program for their support on this evaluation, and all of the program staff at mothers2mothers for providing input into project activities. Thanks are also extended to the interviewers and to the many women who were willing to participate in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 5 publications
2
34
0
Order By: Relevance
“…Our findings are consistent with findings from a survey in South Africa which showed that patients who independently sought HIV testing were more likely to know someone on ARV therapy than those who did not (Mfundisi et al 2005), and are consistent with data from Botswana indicating a rapid increase in testing at VCT centers following the introduction of ARV therapy (Creek et al 2006). South Africa's ''Mothers to Mothers'' is a highly successful model of an approach that takes advantage of this tendency, and has reported high HIV test and PMTCT intervention acceptance in clinics where HIVpositive women teach clients, provide counseling, and dispense drugs for PMTCT (Baek et al 2007). Programs of this type are now beginning in Botswana.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings are consistent with findings from a survey in South Africa which showed that patients who independently sought HIV testing were more likely to know someone on ARV therapy than those who did not (Mfundisi et al 2005), and are consistent with data from Botswana indicating a rapid increase in testing at VCT centers following the introduction of ARV therapy (Creek et al 2006). South Africa's ''Mothers to Mothers'' is a highly successful model of an approach that takes advantage of this tendency, and has reported high HIV test and PMTCT intervention acceptance in clinics where HIVpositive women teach clients, provide counseling, and dispense drugs for PMTCT (Baek et al 2007). Programs of this type are now beginning in Botswana.…”
Section: Discussionsupporting
confidence: 77%
“…Social interventions were defined as any form of social support coming from the male partner, family, peers and community health workers (CHWs). Seven studies examined the effectiveness of peer mentoring interventions as compared to regular/routine PMTCT services [5,6,13,15,16,36,38]. Peer mentoring interventions involved mentor mothers who were also HIV-positive, had had a child recently, had used PMTCT services and were coping positively.…”
Section: Resultsmentioning
confidence: 99%
“…One did not report the timing of interventions [16]. Four of the peer mentoring interventions followed up mother-infant pairs at home and health facilities [13,16,36,38]; one of these studies made phone calls to mothers who had missed their EID appointments [16]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently there are large mhealth initiatives focused on PMTCT in South Africa, including the Mobile Alliance for Maternal Action (www.mobilemamaalliance.org) and mothers2mothers (http://www.m2m.org), among others. The content of these initiatives range from mobile phone provision and SMS messages to peer support from ‘Mentor Mothers’ (22, 23). These initiatives have undergone rapid expansion reinforcing the acceptability of mobile-based initiatives, however rigorous evaluations to assess the effectiveness of interventions have been more limited.…”
Section: Discussionmentioning
confidence: 99%